Neurosensory disturbance after bilateral sagittal split osteotomy: A retrospective study - Sunanda Roychoudhury; Shakil Ahmed Nagori; Ajoy Roychoudhury (Elsevier, 2015)
Aim: To retrospectively evaluate neurosensory disturbance (NSD) after bilateral sagittal split osteotomy (BSSO). Material and methods: A retrospective review was carried out to assess inferior alveolar nerve function in patients treated by BSSO from 2010 to 2013. All patients included in the study were assessed using objective (cotton swabs and pin prick testing) and subjective testing (questionnaire) for inferior alveolar nerve function after a minimum of 1 year of follow-up. Medical records of the patients were used to assess the incidence of NSD in the immediate post-operative period. Results: 15 patients (30 sides) had undergone BSSO during the specified time period. On subjective testing, NSD was reported in 22 operated sides (73.3%) in the immediate post-operative period, while 4 operated sides (13.3%) reported persistent NSD. On objective testing, immediate post-operative NSD was seen in 20 operated sides (66.7%). After a minimum of 1 year follow-up, recovery was seen in 18 operated sides while persistent NSD was seen in 2 operated sides (6.7%). Conclusion: NSD of the inferior alveolar nerve is a common complication after BSSO in the immediate post-operative period. However in a long term, nerve function usually recovers.